Trade Diversion under Selective Preferential Market Access - Borchert, Ingo (World Bank, Washington, DC, 2012)
Through its diverse trade preference schemes, the European Union provides different groups of developing countries with different degrees of market access. This paper is the first to demonstrate empirically that such staggered market access induces sizable trade diversion to the detriment of relatively less preferred beneficiary countries. In particular, preferences granted to African, Caribbean and Pacific economies are shown to impair the export performance of seven developing countries whose products only qualify for basic preferences under the Generalized System of Preferences. Exports to the European Union decline by about 30 percent if the African, Caribbean and Pacific tariff falls by 10 percentage points. In terms of forgone trade volume, losses for these relatively disadvantaged countries amount on average to 9 percent of their total trade with the European Union, depending on the country and its main exports. These intra-developing country distortions are driven by highly substitutable, often labor-intensive commodities.